Adaptation and implementation of the German social–emotional learning programme Papilio in Finland: A pilot study. (27th August 2019) - Koivula, Merja; Laakso, Marja‐Leena; Viitala, Riitta; Neitola, Marita; Hess, Markus; Scheithauer, Herbert
Abstract : This study investigated the cross‐national adaptation and implementation of Papilio, a German social–emotional learning programme, in Finnish early childhood education and care (ECEC) centres. Papilio is a developmentally focused, scientifically based intervention programme focused on preventing behavioural problems and fostering social–emotional competence in children aged 3–7. The aim of this study was to investigate and evaluate the cross‐national adaptation and cross‐cultural adaptation and implementation of Papilio in the Finnish ECEC context. Results from qualitative interviews with one Finnish Papilio trainer, 11 early childhood education (ECE) teachers, two ECE special education teachers and two nursery nurses are supplemented with teachers' and nursery nurses' ( N  = 75) questionnaire data. Qualitative thematic analysis revealed that cultural adaptations were necessary on four levels: accommodation of materials, adaptation of the contents of the materials, structure and delivery. The materials and training contents were culturally adapted, whereas the delivery of the intervention was adapted according to Finnish ECEC practices. The structural adaptation included discarding timeout, due to opposition by some educators. The educators were committed to implementing the programme as instructed and resolving the practical difficulties they encountered. Their motivation to implement Papilio increased as they observed improvements in the children's social–emotional competence during intervention.